Estudo cristalográfico de derivados nitrogenados do ácido 6α, 7β-Diidroxivouacapan-17β-óico - Resende, Jackson Antonio Lamounier Camargos (2003)
Natural products represent an important source of pharmacologically active compounds. The 6 α, 7 β-dihydroxyivouacapan-l7 β-oic (ADV) furanoditerpene acid (ADV) is the main responsible for the analgesic and anti-inflammatory activities presented by the fruits of Pterodon polygalaeflorus Benth, a tree popularly known as “white sucupira”. Derivatives of this compound have been synthesized and studied in order to provide subsidies for understanding the chemical structure-biological activity relationship. In the present work, the crystalline and molecular structures were elucidated, by X-ray diffraction, of the following nitrogenous derivatives of ADV: 6α, 7β-dihydroxyivouacapan-17β-hydroxamic acid (AVHX); 7β -hydroxy-6α -oxovouacapan-17β -amide (POLAM); N-cyclohexyl-7β-hydroxy-6 α -oxovouacapan-17β -amide (POLCHA); N- (7 β -hydroxy-6 α -oxovouacapan-17β-oil) piperidine (POLPIPA). All compounds have intramolecular hydrogen bonds and their crystalline packaging is stabilized by intermolecular hydrogen bonds, with the exception of the POLPIPA compound. A molecule of crystallization water was found in the packaging of the compounds AVHX and POLAM. POLCHA amide crystallizes with two molecules per asymmetric unit. The conformation of the rings of the furanoditerpene skeleton proved to be similar in all the elucidated structures.